Legal Standing Anak di Bawah Umur sebagai Pemohon Dispensasi Nikah dalam Perspektif Maslahah (Studi Putusan Nomor 224/Pdt.P/2024/PA.Pdg) - Hilya Fijra Salsabila; Fauzan (Lembaga Yasin AlSys, 2026)
The legal standing of a minor as an applicant for marriage dispensation has received attention in several studies. However, research on the legal status of a minor who submits an application directly because no parent or guardian is available to act as the applicant, particularly from the perspective of maslahah, remains limited. This study aimed to analyze the legal standing of a minor as an applicant for marriage dispensation in Religious Court Decision Number 224/Pdt.P/2024/PA.Pdg and to examine the judge’s considerations from the perspective of maslahah. This study employed a qualitative approach using normative legal research through a literature review. Legal materials were obtained by examining the court decision, legislation, books, scholarly journal articles, and relevant literature and were subsequently analyzed descriptively and analytically. The results showed that the 17-year-old applicant submitted the application directly because the biological mother had died, the father’s whereabouts were unknown, and no guardian was available to submit the application. The judge accepted and granted the application after considering the applicant’s circumstances on a case-by-case basis, the relationship between the applicant and the prospective husband, and efforts to prevent harm. From the perspective of maqashid al-shariah, granting the dispensation provided benefits in the dimensions of hifz al-din and hifz al-nasl. However, the dimensions of hifz al-nafs, hifz al-‘aql, and hifz al-mal were not optimally fulfilled. These findings emphasize that decisions regarding marriage dispensation applications submitted by minors must consider the specific legal and factual circumstances of each case while comprehensively assessing all dimensions of maslahah. This study contributes to the development of Islamic family law scholarship concerning the relationship among legal standing, child protection, and maslahah in marriage dispensation cases.